Evaluation of a Combined Explicit–Implicit Approach to Teach Grammatical Forms to Children With Grammatical Weaknesses - Finestack, Lizbeth; Engman, Jennifer; Huang, Timothy; Bangert, Katherine J.; Bader, Kaela (American journal of speech-language pathology, 2020)
Purpose Many children with developmental disorders experience difficulty mastering grammatical forms, including children with developmental language disorder and a subset of children with autism spectrum disorder (ASD). One of the key language features in both of these populations is a weakness in the expressive use of grammatical forms. There is a paucity of studies that evaluate the effectiveness of interventions targeting grammatical forms for populations other than developmental language disorder. The current study evaluated a combined explicit-implicit intervention approach to teach grammatical forms to children with ASD symptomology. Method Researchers used a single-subject, nonconcurrent multiple baseline, A-B-C study design. Three children with characteristics of ASD (2 with formal diagnoses) between the ages of 5 and 9 years participated in treatment targeting a weak grammatical structure. After baseline, each participant completed a series of treatment sessions that comprised implicit instruction, followed by a series of treatment sessions that incorporated explicit instruction. Accuracy of use was assessed during each session across baseline, implicit-only, and explicit-implicit conditions as well as 1 week, 1 month, and 2 months posttreatment. Results All participants produced target forms with low accuracy across baseline and implicit-only treatment sessions. Within three explicit-implicit treatment sessions, all participants demonstrated a marked increase in level and upward trend in their production accuracy. Gains in accuracy were maintained 2 months posttreatment for 2 of the 3 participants. Conclusions The current study provides preliminary evidence to support the use of explicit approaches to teach grammatical forms to children with ASD symptomology and motivates further investigation in this area.